Reductive prodrug and AIE copolymer nanoparticle for monitoring and chemotherapy - Zigui Wang; Guilin Li; Qiaohui Zhao; Guangyu Fu; Zengli Yang; Guojun Zhang (BMC Cancer, 2024)
Abstract Polymeric micelle systems for drug delivery, monitor and chemotherapy have gained significant attention, and reductive polymeric micelle systems have become particularly attractive due to their controlled release behavior without additional assistance. However, there are challenges in accurately controlling drug and probe release from the nanoparticles and determining the loading content of drug and probe. To address these issues, we have developed a reduction-responsive Pt(IV) prodrug-based polymeric delivery system that can be dynamically monitored using aggregation-induced emission luminogens (AIE) based bioprobes. These polymeric micelle can self-assemble into nanoparticles and release both bio-active Pt(II) drug and bio-probe upon reduction activation. TPE molecules released in the inner endo/lysosomal microenvironment aggregate and fluoresce upon irradiation, thus allowing real-time tracking of drug biodistribution without additional contrast agents. Advantages of this system include position-specific chemical bond cleavage, control of platinum content, and monitoring of drug reduction and biodistribution.